Taxpayer Satisfaction with the Use of the Core Tax System: A Qualitative Analysis of the Effectiveness of Tax Administration Modernization (International Forum of Researchers and Lecturers, 2025)
This study explores taxpayer satisfaction with the implementation of the Core Tax system introduced by the Directorate General of Taxes (DGT) in Indonesia since 2021. As part of a broader digital transformation initiative, the Core Tax system replaces the legacy infrastructure to enhance the efficiency, accessibility, and compliance of tax administration. The research adopts a qualitative approach, utilizing in-depth interviews with 15 corporate and individual taxpayers who have actively used the system for a minimum of one year. Data were analyzed using thematic analysis to identify key factors influencing user satisfaction. The findings reveal that the majority of respondents expressed positive experiences with the Core Tax system, particularly highlighting improvements in processing speed, ease of access, and the intuitiveness of the user interface. These aspects were perceived as significant enhancements compared to the previous system, contributing to a more streamlined and responsive tax service. Nonetheless, several challenges were identified, including concerns over system stability, occasional technical disruptions, and a lack of comprehensive public outreach and education regarding system features and usage. These insights suggest that while the Core Tax system has made notable progress in modernizing tax administration, further optimization is needed to address technical and socialization gaps. The study recommends that the DGT intensify efforts in system stabilization, user support, and digital literacy campaigns to ensure broader acceptance and effective utilization. Additionally, continuous feedback mechanisms should be established to monitor taxpayer experiences and guide iterative improvements. This research contributes to the discourse on e-governance and digital public service delivery, offering practical recommendations for enhancing taxpayer engagement and satisfaction. It also serves as a reference for policymakers and practitioners aiming to strengthen digital infrastructure in fiscal governance.